Current development of IMT-2000 in China. - Shumin, C.
This article describes the current development of mobile communications in China, including market demand, operators, and technologies. The reasons China put great emphasis on IMT-2000 research and development are discussed. An IMT-2000-related organization structure is given, and their different responsibility and latest progress are also described. Finally, the author gives some viewpoints on IMT-2000
Keywords: China; IMT-2000.; International standard; Market demand; Mobile communications; Operators; Organization structure; Planning; Research and development